Beginning Kinect programming with the Microsoft Kinect SDK - Ashley, James, ....-; Webb, Jarrett, ....- (New York : Apress, 2012)
Table of Contents Getting Started with Kinect Application Fundamentals Depth Image Processing Kinect Skeletons Advanced Skeleton Tracking Kinect Gestures Speech Beyond the Basics